The effect of fruit ripening, altitude and harvest year on volatile compounds of virgin olive oil obtained from the Ayvalık variety. (9th December 2015) - Toker, Cem; Aksoy, Uygun; Ertaş, Hasan
Abstract: Research was aimed at the determination of the fatty acid and volatile composition of oils made from Ayvalık olives grown in Turkey and the effects played by maturity and altitude on composition. Samples were obtained from five orchards located at 25, 74, 132, 202 and 250 m above sea level in Edremit (Balıkesir, Turkey). Olive samples were harvested at three maturity levels (green, semi‐black and black) in 2007 and 2008 to extract the oil. E‐2‐hexenal was found to be the main volatile compound in all samples and its concentration decreased as maturity progressed. Hexanal and E‐1‐pentene‐3‐one were also at high levels in all samples. Levels of all aroma compounds, except E‐2‐hexenol and hexylacetate, decreased with the degree of ripeness. Altitude plays an evident but less intense effect on the volatile composition. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The research aimed at determination of olive oil quality, namely volatile compounds forming through the lipoxygenase pathway of Ayvalık olive variety grown in its original location. E‐2‐hexenal decreased during maturation. E‐2‐hexenal, hexanal and 1‐penten‐3‐one were dominant in virgin olive oils.